Efecto del extracto de Trichocereus pachanoi sobre aprendizaje y memoria espacial en Rattus novergicus var. Albinus - Rodriguez Vega, Juan Luis (2023)
Throughout the history of mankind, hallucinogens or entheogens have been used for various purposes from religious worship. Its physiological study is not easy because it is concoctions prepared based of plant extract, whose intake develops variable effects on emotions and learning. The objective was to: evaluate the effect of Trichocereus pachanoi extract on spatial memory in Rattus norvegicus var. albinus. At the methodological level: a growing stimulus design was developed where four similar groups of 5 rats were ordered, grouping into Problem I, II and III groups; who were given the extract orally at different concentrations and the control group was not treated assessing the spatial memory in Morris’ water labyrinth. The following results were: found in the first place the rats presented a similar average time to develop latency in the acquisition phase and equivalent times were observed in the retention phase; When applying the 10% and 20% dose, the learning indices vary showing slight decrease between them; and at the highest concentration dose 30%, there was a greater decrease in the latency time of the acquisition phase, presenting long-term depression. It can be concluded that there was an effect equivalent to long-term depression in the experimental subject, evidenced in the duration of motor behavior in Morris’ water labyrinth, through learning indices.